1986
DOI: 10.1128/aac.30.5.774
|View full text |Cite
|
Sign up to set email alerts
|

Disk diffusion susceptibility of Branhamella catarrhalis and relationship of beta-lactam zone size to beta-lactamase production

Abstract: We tested 231 isolates of BranhameUa catarrhalis for P-lactamase production and drug susceptibility by the National Committee for Clinical Laboratory Standards disk diffusion method. The nitrocephin disk (Cefinase) identified 13-lactamase in 98% of the enzyme-producing strains, and a zone diameter of inhibition of <29 mm for penicillin correctly predicted the presence of P-lactamase in 99% of the isolates. No resistance to erythromycin, tetracycline, trimethoprim-sulfamethoxazole, or amoxicillin-clavulanic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Our study showed the same general trend of higher ampicillin resistance among BRO-1-producing strains reported previously (8,10,15); however, the wide range of ampicillin MICs observed for BRO-1 strains was unexpected and suggests that factors other than enzyme type determine antibiotic susceptibility.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Our study showed the same general trend of higher ampicillin resistance among BRO-1-producing strains reported previously (8,10,15); however, the wide range of ampicillin MICs observed for BRO-1 strains was unexpected and suggests that factors other than enzyme type determine antibiotic susceptibility.…”
supporting
confidence: 58%
“…Although substrate hydrolysis rates of BRO-1 and BRO-2 enzymes are similar, BRO-1-producing isolates are more resistant to penicillins than BRO-2 strains (8,10,15). The higher ␤-lactam minimum inhibitory concentrations (MICs) associated with BRO-1 strains have been attributed to larger amounts of enzyme produced (15).…”
mentioning
confidence: 99%
“…Indeed, the authors of this report emphasized the need for a systematic investigation of disk diffusion susceptibility testing of B. catarrhalis with the aim of clearly defining an optimum test method and suitable interpretive criteria. Recently, there have been two published studies which have addressed this issue (13,23). In one study, however, only 25 strains of B. catarrhalis were examined, and 15 of these were not clinical isolates (23).…”
Section: Discussionmentioning
confidence: 99%
“…They did not find strains with poor growth when agar was incubated in ambient air. Luman et al (27) studied 231 isolates grown on Mueller-Hinton agar, using CLSI disk contents. Like our study, they too noted that a proportion of strains, 11% in their case, grew poorly in ambient air, and required retesting in 5% CO 2 .…”
Section: Discussionmentioning
confidence: 99%